Photoactivatable Hsp47: A Tool to Regulate Collagen Secretion and Assembly. Issue 9 (28th February 2019) - Khan, Essak S.; Sankaran, Shrikrishnan; Paez, Julieta I.; Muth, Christina; Han, Mitchell K. L.; del Campo, Aránzazu
Abstract: Collagen is the most abundant structural protein in mammals and is crucial for the mechanical integrity of tissues. Hsp47, an endoplasmic reticulum resident collagen‐specific chaperone, is involved in collagen biosynthesis and plays a fundamental role in the folding, stability, and intracellular transport of procollagen triple helices. This work reports on a photoactivatable derivative of Hsp47 that allows regulation of collagen biosynthesis within mammalian cells using light. Photoactivatable Hsp47 contains a non‐natural light‐responsive tyrosine (o‐nitro benzyl tyrosine (ONBY)) at Tyr383 position of the protein sequence. This mutation renders Hsp47 inactive toward collagen binding. The inactive, photoactivatable protein is easily uptaken by cells within a few minutes of incubation, and accumulated at the endoplasmic reticulum via retrograde KDEL receptor‐mediated uptake. Upon light exposure, the photoactivatable Hsp47 turns into functional Hsp47 in situ. The increased intracellular concentration of Hsp47 results in stimulated secretion of collagen. The ability to promote collagen synthesis on demand, with spatiotemporal resolution, and in diseased state cells is demonstrated in vitro. It is envisioned that photoactivatable Hsp47 allows unprecedented fundamental studies of collagen biosynthesis, matrix biology, and inspires new therapeutic concepts in biomedicine and tissue regeneration. Abstract : The drowsy chaperone gets awake . Hsp47 is a chaperone protein with a fundamental role in the folding, stability, and intracellular transport of procollagen triple helices. Here, a light‐responsive Hsp47 recombinant protein, engineered to control in situ the production and assembly of cellular collagen is demonstrated. This light‐driven tool enables unprecedented fundamental studies of collagen biosynthesis and associated diseases.